Conformational energy landscape of the ritonavir molecule - Chakraborty, Debayan; Sengupta, Neelanjana; Wales, David J. (Journal of Physical Chemistry B, 2016)
Conformational polymorphism of ritonavir, a well-known pharmaceutical drug, is intricately linked to its efficacy in the treatment of acquired immunodeficiency syndrome (AIDS). Polymorphic transition from the crystalline form I to form II leads to the loss of bioactivity. The constituent ritonavir molecules adopt a trans configuration about the carbamate torsion angle in the form I crystal, and a cis configuration in the form II crystal. Investigating the energetics and mechanistic features of conformational transitions at the single molecule level is a key step toward decoding the complex features of the solid state polymorphism. In this work, we employ the energy landscape framework to investigate the conformational transitions of an isolated ritonavir molecule. The landscape is explored using discrete path sampling (DPS) and visualized in terms of disconnectivity graphs. We identify two distinct funnels corresponding to the two molecular forms that are identified by crystallography. The two regions can be reliably distinguished using the carbamate torsion angle, and the corresponding interconversion rates are predicted to follow Arrhenius behavior. The results provide mechanistic insight into pathways for cis <-> trans interconversion at the molecular level and may also help in elucidating the polymorphic transitions in the crystal state.